Improving The Ability to Calculation of Cost of Goods Sold on MSMEs in Bojongsoang Village, Bandung City - Pupung Purnamasari; Riyang Mardini; Annisa Nadiyah Rahmani; Irena Paramita Pramono; Tiara Mustikasari; Ilvia Restu Utami; Laila Sugiharta (Kajian Akuntansi, 2022)
National economic recovery needs support from various parties, not only from the government but also from academics who actually have a duty to serve the community to build scientific progress for the welfare of society. This service activity has a goal, namely (1) providing understanding to SMEs in Bojongsoang Village, Bandung City about the importance of calculating the cost of goods sold, (2) providing training and assistance for SMEs in Bojongsoang Village, Bandung City, so that they are able to calculate the cost of goods sold correctly. The implementation method used in this service is the lecture method, discussion method, and simulation method. The results of this service activity influenced the increase in score by 35.22% on the level of understanding of the training participants' cost of goods sold, meaning that this training on calculating the cost of goods sold affected the participants of MSMEs in Bojongsoang Village, Bandung City.